Psychosocial Aspects in Teaching Communication Issues of Learners - Kulpynay, Duisenbay; Bagdad, Zhubanova; Zhansaya, Issayeva; Kulyash, Zhubanova; Sandygash, Mettibayeva; Balabek, 3Saktaganov (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, the fact of lack of knowledge of bilingualism due to the changed volume ratio in the teaching of writing is becoming more and more obvious, specially to learners with intellectual disabilities. This fact is marked by the emergence of complex processes is interference and convergence of speech, which are sources of better speaking and writing in bilingualism. The purpose of the study is to identify the specific difficulties of teaching writing to younger bilingual schoolchildren with ID and to develop a productive speech therapy system for the prevention and correction of violations of higher mental functions that they have. The object of research is the features of teaching children with speech deficiency and with ID to writing in bilingual conditions. The subject of the research is the process of preventing and overcoming problems in the bilingual conditions of teaching children with speech and ID functions deficiency.